The role of extracellular vesiclesin multiple myeloma - Ferreira, Bruna Velosa (2022)
Abstract: Multiple myeloma (MM) is a hematological malignancy of clonal antibody-secreting plasma-cells(PC). MM diagnosis and risk stratification rely on tumoral assessment via bone marrow (BM) biopsy, which is an invasive procedure prone to sample bias. Liquid biopsies, such as extracellular vesicles (EV) in peripheral blood(PB), hold promise as new minimallyinvasive tools. Real-world studies analyzing patient-derived EV proteome are rare. Here, we characterizePB and BMEV protein content from acohort of 102monoclonal gammopathiespatients routinely followed in theclinic. A total of 223 PB and 111BM samples were included.We investigated whether EV protein and particle concentrationcould predict MM patient prognosisandfoundthat high EVprotein/particle (EVc> 0.6 μg/108particles) levelis related to poorer survival and immune dysfunction.These results were supportedat protein level by mass spectrometry.We report a set of PB EV-proteins (PDIA3, C4BPA, BTN1A1, APRIL, PSMB8 and PDE8B) with new biomarker potential for myeloma patientoutcomes. High proteomic expression similarity between PB and BM matched pairs were found, suggestingthe use of circulating EV as a personalized counterpart of BM EV proteome. Overall, we found that EV protein content couldberelated to patient outcomes, suchassurvival,immune dysfunction,andpossiblyspecific treatment response.